Pengaruh Bauran Pemasaran Jasa dan Citra Merek terhadap Reputasi Penyelenggara Jasa Pendidikan - lady diana warpindyastuti (Universitas Bina Sarana Informatika, 2019)
Marketing strategy is needed in any business, no exception in the business of education. But for marketing public schools and school image is needed to shape the reputation of the school so that parents are interested in sending their children to the state school. Madrasah Ibtidaiyah Negeri 18 Jakarta also attaches importance to the Service Marketing Mix and Brand Image to build its reputation. So the purpose of this research is to find out how big the influence of Service Marketing Mix and Brand Image both separately (partial) and jointly (simultaneously) on the Reputation of Educational Service Providers in Madrasah Ibtidaiyah Negeri 18 Jakarta. This study uses a quantitative method with a questionnaire of 83 samples from 480 parents of students at Madrasah Ibtidaiyah Negeri 18 Jakarta. Then, the regression equation formula is determined after the validity test, reliability test, normality test, multicollinearity test, heterokedastisitas, and correlation test on each questionnaire results and scores for both the dependent variable and the independent variable. The results showed that the Marketing Mix of Services and Brand Image both separately and together significantly affected the Reputation of Providers of Educational Services in Jakarta 18 Madrasah Ibtidaiyah with 99% accuracy.